ANALISIS BIBLIOMETRIKA MENGGUNAKAN HUKUM LOTKA PADA PRODUKTIVITAS PENULIS ARTIKEL BIDANG PERTANIAN DI INDONESIA - Peggy Antonette Soplantila; Imas Sukaesih Sitanggang; Sulistyo Basuki (Jurnal Pustakawan Indonesia, 2017)
AbstractThe purpose of this research is to know the author's productivity pattern of article in the field of agriculture in Indonesia 2006-2015 using Lotka’s Law. The data of this research were taken from national journal accredited by the Ministry of Research, Technology and Higher Education which can be accessed from http://www.kopertis12.or.id. From 2006-2015, it is found that there are 2650 authors and 4141 articles on Agriculture. Assessment author’s participation was done by using ‘straight count’.The Lotka theoretical value use the formula of yx=C/xn.. C is a constant and n is exponent. Based on the calculation with Lotka’s law, it is found that C=0.80773 and n= 2.81500. The result shows that the percentage of the authors giving contribution to 1 article is 80.77%. Test of Kolmogorov-Smirnov results shows that the maximum deviation is 0.08396 with critical value (with α = 0.05) 0.02642, it shows that the maximum deviation is bigger than critical value. Therefore, the null hypothesis is rejected and concluded that the dataset does not follow Lotka’s law (there is a significant difference between the Lotka’s law theoretic distribution and the distribution of article author in the field of Agriculture). Keywords: Agriculture Science, Author Productivity, Bibliometrics, Lotka Law